Understanding as a Concept in Education: Conceptions and Alternative Interpretations - Amukowa, Wycliffe; Gunga, Samson O.; Ayuya, Caroline V. (MCSER Publishing, Rome-Italy, 2014)
Education has largely been conceptualized as transmission and acquisition of knowledge, skills, attitudes and values so as to facilitate desirable behavior. This conceptualization presupposes knowledge, skills, attitudes and values as sufficient conditions for desirable behavior; however this paper argues that these are necessary but not sufficient without Understanding. What understanding is or is not, and how it is to be justified as an educational condition demands explicit attention.
Keywords: Education; Conceptions; Concept